Contribuições de Erving Goffman para os estudos lingüísticos - Fernandes, Cleudemar Alves (Cadernos de Linguagem e Sociedade, 2010)
This paper has the objetive to present the theories of Erving Goffman that contribute to linguistic analysis. In this perspective, an effort was made in order to include most of Golffman’s works pointing out the central issues that deal with discourse analysis in social interaction. These theoretical considerations, besides approaching specific issues of Social Psychology and Sociology, consider proposals of studies in Interactional Sociolinguistics, Conversation Analysis and Discourse Analysis.